Real-life data on potential drug-drug interactions in patients with chronic hepatitis C viral infection undergoing antiviral therapy with interferon-free DAAs in the PITER Cohort Study - Kondili, Loreta A. (PLoS One, 2017)
BACKGROUND: There are few real-life data on the potential drug-drug interactions (DDIs) between anti-HCV direct-acting antivirals (DAAs) and the comedications used. AIM: To assess the potential DDIs of DAAs in HCV-infected outpatients, according to the severity of liver disease and comedication used in a prospective multicentric study. METHODS: Data from patients in 15 clinical centers who had started a DAA regimen and were receiving comedications during March 2015 to March 2016 were prospectively evaluated. The DDIs for each regimen and comedication were assigned according to HepC Drug Interactions (www.hep-druginteractions.org). RESULTS: Of the 449 patients evaluated, 86 had mild liver disease and 363 had moderate-to-severe disease. The use of a single comedication was more frequent among patients with mild liver disease (p = 0.03), whereas utilization of more than three drugs among those with moderate-to-severe disease (p = 0.05). Of the 142 comedications used in 86 patients with mild disease, 27 (20%) may require dose adjustment/closer monitoring, none was contraindicated. Of the 322 comedications used in 363 patients with moderate-to-severe liver disease, 82 (25%) were classified with potential DDIs that required only monitoring and dose adjustments; 10 (3%) were contraindicated in severe liver disease. In patients with mild liver disease 30% (26/86) used at least one drug with a potential DDI whereas of the 363 patients with moderate-to-severe liver disease, 161 (44%) were at risk for one or more DDI. CONCLUSIONS: Based on these results, we can estimate that 30–44% of patients undergoing DAA and taking comedications are at risk of a clinically significant DDI. This data indicates the need for increased awareness of potential DDI during DAA therapy, especially in patients with moderate-to-severe liver disease. For several drugs, the recommendation related to the DDI changes from “dose adjustment/closer monitoring”, in mild to moderate liver disease, to “the use is contraindicated” in severe liver disease.